SWOT ANALYSIS OF MANUFACTURING UNIT PRODUCTION PERFORMANCE IN SMK NEGRI 7 SURABAYA INCREASING THE QUALITY OF GRADUATES - Rintis Yona (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
The impact is that many of the SMK, SMA and MA graduates have not been able to compete in the business world and in the Industrial world especially the SMK that dominates Surabaya's open unemployment rate of 11.74 percent, from the data indicating that there is a poor relationship between education and employment. The public policy model implemented in SMKs in Surabaya including SMK N 7 Surabaya is still centralized at the central of government. The impact of these policies is the implementation of policies that seem slow and not on target. The relationship between schools and business actors also does not work well if it is based on not absorbing graduates of SMK N 7 Surabaya in the fields of work around the school environment. This research intends to examine more deeply the public policy of the management of production units in SMKs and the models that can improve the management of SMK industrial units, where later than reporting these SMK production units becomes clear, it is hoped that the performance of these production units will also increase. The public policy evaluation model which is used as the basis for this research theory is to compare the results obtained with the objectives or targets of public policy determined to assess how far a public policy can produce results. Based on the research that has been done, a conclusion can be drawn that SMK N 7 Surabaya is in an unfavourable condition in using its internal strengths to overcome internal weaknesses. The public policy model in the management of the production unit of SMK 7 N Surabaya as a whole is in the good category with average scores, an average of 77.33%.